English Language Female Teachers' Professional Competencies in virtual classes - Alshmsan, Mashael Ebraheem; Alnusian, Abdurahman Muhammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to know the professional competencies required for English language female teachers in virtual classes and to know the nature of online training programs and ways to develop them in light of the training needs of teachers, and the training needs of English language teachers were determined using the interview, observation, and review of the teachers' portfolios and the sample consisted of 3 cases. For English language teachers, it included all stages of general education (two teachers from the secondary stage, two teachers from the intermediate school, and two teachers from the primary school) and one case from the English language supervisors (two English language supervisors). The study used the qualitative approach. The results of the study showed that the most important professional competencies required for English language teachers in virtual classes are the teacher’s familiarity with technology and her ability to time management skills and the skill of virtual classroom management. The results also showed that the teacher's role in virtual class differs than a mentor, guide and assistance to students in self-learning. The results showed the pros and cons of the nature of online training programs and the training needs of teachers, and in the light of that a proposed concept was constructed for developing online training programs and providing appropriate recommendations.
Keywords: professional competencies; virtual classes; training needs